Lao She's Beijing-style Language Reflects the Changes of the Times and the Feelings of the Family and Country: -- Take, For Example, The Image of a Citizen in "The Teahouse" - Sheng, Bao (Transactions on Social Science, Education and Humanities Research, 2024)
Lao She is a famous novelist in modern China and has the reputation of "People's Artist". His play "Teahouse" is considered by Cao Yu to be "a treasure in the history of Chinese drama". In "Teahouse", Lao She portrays a series of citizens represented by Wang Lifa, who grew up in Beijing and have a rich "Beijing flavor" in their language. Lao She is also using these original "Beijing flavor" language, through the mouth of these citizen images, to show the changes of modern China and Lao She's strong feelings for his family and country.